O futuro do ePrivacy - Raminhos, Patrícia dos Santos (2021)
The present master´s dissertation will focus on the Proposal for a Regulation of the European Parliament and of the Council concerning the respect for private life and the protection of personal data in electronic communications, also known as ePrivacy Regulation. The cornerstone of my dissertation will rely on article 6 of the Proposed Regulation, inciding on the processing of eletronic comunications content and metadata. Article 6, after several amendments, firts by the European Parliament and then by the succesives European Council presidencies, had constitute an obstacle to technological development in a vital sector of the digital economy, such as the eletronic communications sector, once it was based on an approach which established a general prohibition for processing of eletronic communications data, with very strict exceptions. After four years of discussion and under the portuguese presidency, the ePrivacy text was finally aproved in the European Council, starting now the negotiations with the European Parliament and with the European Comission. This new text, even if not fully aligned with GDPR and with industry expectations is, when compared with its predecessors, the text that better accomplishes the balance between a high level of protection of electronic communication data and metadata with the desired technological development.